(untitled) (Economic and Political Thought, 2014)
Alternative currencies also known as local currencies are becoming more and more popular means of payment. Across the world, there are currently about four thousand alternative currencies. They are not issued by states, but by counties, cities and even by persons. A dynamic growth of the Internet and technological and communication innovations contributes to the development of digital alternative currencies due to a possibility of creating platforms, exchange webpages and the establishment of on-line communities. The subject of the article is an analysis of an alternative currency as the common good on the basis of literature research. To that end, the term of ‘common’ is explained. Next, the term ‘alternative currency’ and examples of such currencies are presented.